A critical review of interdisciplinary perspectives on the paradox of prosocial compared to antisocial manifestations of empathy. (December 2020) - Guthridge, Michaela; Mason, Paul H.; Penovic, Tania; Giummarra, Melita J.
Empathy is the ability to experience affective and cognitive states of another person, whilst maintaining a distinct self, in order to understand the other. It is a multidimensional phenomenon, ranging from vicarious distress to near complete understanding, with many shades in between. As an almost universal and integral human construct, empathy has been considered in many disciplines and contexts, from evolution to gender, politics, economics, ethics, human rights and neuroscience. Each of these disciplines offers a range of definitions of empathy, and provides unique insights into the role of empathy in achieving different types of social outcomes, including those with both prosocial and antisocial intentions. The conceptualization generated from interdisciplinary perspectives is important because it allows us to identify commonalities that could be mobilized synergistically to achieve greater social benefit through prosocial empathy. This review discusses the benevolent and malevolent manifestations of empathy from the perspective of social, legal and psychological sciences in order to lay the foundation for a theoretical discussion on the potential of harnessing prosocial empathy to advance equality and non-discrimination.